PENGARUH LINGKUNGAN PENGENDALIAN TERHADAP FRAUD PADA LAPORAN KEUANGAN PEMERINTAH DAERAH KOTA PAREPARE - Jumriani, Jumriani; Anwar, Anwar (Universitas Muhammadiyah Parepare, 2019)
The Government Internal Control System (GICS), which is considered weak and inappropriate, can commit fraud. The author takes the title